Social Consensus and the Meta-Regulation of Land-Taking Disputes in Vietnam /John Gillespie. - Gillespie, John.
Scholars have shown that Vietnam’s authoritarian regime responds to citizens. They speculate that this responsiveness may arise from rules within the party regime, citizen engagement, and a strategy that offers preferential treatment to a narrow group of supporters. This article adds to this literature by showing how intermediaries leverage their personal relationships within the party and state to circumvent formal legal and political hierarchies and broker solutions to complex land-taking cases. It uses ethnographic studies of land-taking disputes to explore the limits of law and legal authority in resolving these disputes and analyze how intermediaries use informal dialogical exchanges to sensitize officials to the needs of land users and to increase land compensation. Dialogue not only resolves misunderstandings and promotes understanding, more importantly it gives the parties a common set of norms and assumptions to work toward. However, such dialogue has not completely succeeded in resolving the complexities of land-taking cases in Vietnam.